Use of medicinal plantas among university students in Ribeira Valley (Research, Society and Development, 2021)
To identify the use of medicinal plants among university students in health science courses in Ribeira Valley. Exploratory, descriptive, cross-sectional study with a quantitative approach, carried out with students in the final year of bachelor's degrees in nursing, physiotherapy, pharmacy and nutrition. Sociodemographic information and information on the use of medicinal plants were collected. The 76 students participated in the study, 38.2% from the nursing course, 28.9% from physiotherapy, 19.7% from pharmacy and 13.2% from nutrition. Participants are considered to be predominantly female, aged < 25 years, who are denied to use medicinal plants and were unaware of the National Policy on Integrative and Complementary Practices. Most of them believe in the effectiveness of medicinal plants in the treatment of diseases and more than half reported that during graduation the topic “medicinal plants” was not addressed in classes, events and/or other academic activities. Bilberry was the most consumed plant among students, with the purpose of treating nausea, malaise, stomachache, digestion and liver pain. Although students reported, believing in the therapeutic effect of medicinal plants, more than half reported not using them. In this context, it is essential to expand discussions on the subject in the academic context, as it may reflect on the performance of future professionals, especially those inserted in Primary Care.